Speaking to the Deaf: Herodotus, his Audience, and the Spartans at the Beginning of the Peloponnesian War - Stadter, Philip A. (Histos, 2012)
This paper argues that Herodotus hoped that his account of his investigations, among other purposes, would warn his contemporary audience of listeners and readers of the dangers of imperialist ambitions not only in Athens but also in Sparta. Through key episodes and personalities (Tegea, Cleomenes, Leonidas, the Isthmus wall), Herodotus portrays the Spartans as paradoxically both imperialist and isolationist. He implies that Greeks should not trust Sparta as a champion of Greek freedom from Athenian tyranny, but many did not heed the warning.